2019
DOI: 10.1111/efp.12519
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of the powdery mildew fungus infecting rubber trees in China

Abstract: Powdery mildew is a foliar disease of rubber trees. It is one of the most important leaf diseases in rubber plantations worldwide. The causal agent of this powdery mildew, previously known as Oidium heveae, has been identified under various names. To precisely identify the causal agents of this disease, 57 conidial samples were collected from 2013 to 2017 in Hainan, Yunnan and Guangdong provinces, the main rubber tree planting regions in China. Based on morphological observations using light and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The optimal germination temperature was estimated to be 23.2°C, which is very close to the previous report of the optimal temperature for rubber mildew conidial germination being 25°C (Liu et al, 2014). The present study also shows why rubber powdery mildew occurs annually in China (Wu et al, 2019 found to affect the rate of rubber tree leaf development (Zhai et al, 2019). This was also observed in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The optimal germination temperature was estimated to be 23.2°C, which is very close to the previous report of the optimal temperature for rubber mildew conidial germination being 25°C (Liu et al, 2014). The present study also shows why rubber powdery mildew occurs annually in China (Wu et al, 2019 found to affect the rate of rubber tree leaf development (Zhai et al, 2019). This was also observed in our study.…”
Section: Discussionsupporting
confidence: 89%
“…. In China, the disease was first recorded in 1951, and it now occurs annually in all rubber plantations (Wu et al, 2019).…”
mentioning
confidence: 99%
“…Out of the 24 specimens included in the genome-scale analyses, only 10 had their nrDNA loci sequenced by Sanger sequencing, and only one of them, originally recognized as Oidium heveae HO-73, had all the three loci sequenced prior to this study ( Table 4 ). (HO-73 should be identified as an isolate of E. quercicola based on Wu et al, 2019 ; see below.) Subsequently, we attempted to extract the missing nrDNA loci from the published genome assemblies for inclusion in the nrDNA phylogenetic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of climatic factors, rubber trees may suffer from a variety of pests and diseases, most typically powdery mildew and anthracnose, during the tender leaf stage. Rubber tree anthracnose is caused by Colletotrichum gloeosporioides and Colletotrichum acutatum infections, whereas rubber tree powdery mildew is caused by Oidiumheveae [36,37]. The lesion features of the two diseases are highly similar, making them difficult to distinguish, which has a certain impact on the classification results of the network model.…”
Section: Introductionmentioning
confidence: 99%